1983
DOI: 10.1111/j.2044-8279.1983.tb02565.x
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Picture Upon the Readability of a School Science Topic

Abstract: Summary. The effect of picture upon the readability of a specially written science topic was studied. 338 14‐year‐old children studying CSE Biology in six comprehensive schools completed a cloze test during their study and an objective items recognition test 15 minutes afterwards. Analysis of variance performed on post‐test scores showed that when pictures were present the topic was more easily remembered. However, pictures played little part in the children's performance on the cloze test. It is concluded th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
2
6

Year Published

1987
1987
2013
2013

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(28 citation statements)
references
References 0 publications
1
19
2
6
Order By: Relevance
“…These results indicate that pictures that do not help to explain arbitrary relationships can actually interfere with the retention of explanatory verbal elaborations that could facilitate comprehension. These findings may help explain why other studies have failed to demonstrate facilitative effects of pictures on comprehension (e.g., Reid, Briggs, & Beveridge, 1983). Although other research (e.g., Peeck, 1974) has indicated that pictures can adversely affect learning if they contain information contradictory to a text, the present findings suggest that such interference effects can occur even when the pictures do not contradict any of the information presented verbally.…”
Section: Pictorial Elaboranon 287contrasting
confidence: 44%
“…These results indicate that pictures that do not help to explain arbitrary relationships can actually interfere with the retention of explanatory verbal elaborations that could facilitate comprehension. These findings may help explain why other studies have failed to demonstrate facilitative effects of pictures on comprehension (e.g., Reid, Briggs, & Beveridge, 1983). Although other research (e.g., Peeck, 1974) has indicated that pictures can adversely affect learning if they contain information contradictory to a text, the present findings suggest that such interference effects can occur even when the pictures do not contradict any of the information presented verbally.…”
Section: Pictorial Elaboranon 287contrasting
confidence: 44%
“…À plusieurs reprises, l'effet de l'illustration a ét é mesuré à l'aide du test critérié à choix multiple : Weintraub (1960), Pederson (1970), Weisberg (1970), Goldberg (1974), Moore (1974), Holliday (1975), Rasco, Tennyson & Boutwell (1975), Holliday & Harvey (1976), Jahoda et al (1976), Kauchak, Eggen & Kirk (1978), Thomas (1978), Omaggio (1979), Koran & Koran (1980), Sewell & Moore (1980), Rice, Doan & Brown (1981), Reid, Briggs & Beveridge (1983). Les réponses à un tel test -d'où sa popularité -sont standardisées et faciles à quantifier : le lecteur doit choisir parmi plusieurs réponses possibles (habituellement quatre) celle qui convient.…”
Section: «Illustrations Facilitate Learning the Information In The Wrunclassified
“…Le test de closure est un autre moyen pour mesurer l'impact de l'illustration sur la compréhension du lecteur (Rankin & Culhane (1970), Bluth (1972), Reid, Briggs & Beveridge (1983), Newton (1983)). Ce test consiste à présenter au lecteur un texte mutilé où chaque n ieme (normalement : 5 eme ) mot est remplacé par un tiret.…”
Section: «Illustrations Facilitate Learning the Information In The Wrunclassified
See 1 more Smart Citation
“…The general form of the stellar IMF has been observationally established, while the situation remains unclear across the hydrogen-burning limit (Reid 2005). Infrared (IR) survey data (e.g., Bouvier et al 1998;Lodieu et al 2005Lodieu et al , 2006aLodieu et al ,b,c, 2007Luhman 2004b;Luhman et al 2006;Moraux et al 2003;Muench et al 2003Muench et al , 2007, have produced reliable statistics for substellar objects.…”
Section: Introductionmentioning
confidence: 99%